Hemostatic Effects of Oral Contraceptives in Women who Developed Deep-vein Thrombosis while Using Oral Contraceptives - Bloemenkamp, Kitty W. M.; Rosendaal, Frits R.; Helmerhorst, Frans M.; Koster, Ted; Bertina, Rogier M.; Vandenbroucke, Jan P. (Thrombosis and Haemostasis, 1998)
Objective: Comparison of the effect of oral contraceptives on hemostatic variables in venous thrombosis patients (thrombosis while using oral contraceptives) with the effect in healthy control subjects. Our aim was to assess whether some of these effects were more pronounced in women who had suffered thrombosis, i.e., whether these were “hemostatic hyperresponders”. Study Design: A population-based case-control study, the Leiden Thrombophilia Study. Materials and Methods: We investigated 99 pre-menopausal women, age 15-49 years, who had used oral contraceptives at the time of a first, objectively confirmed episode of deep-vein thrombosis. They were not pregnant, nor in puerperium, nor had had a recent miscarriage, and were not using injectable progestogens, nor suffering from inherited coagulation defects. The median time between occurrence of deep-vein thrombosis and venepuncture was 18 months, and 30 of the 99 women were still using oral contraceptives, while 69 had discontinued oral contraceptive use. In addition, a group of 153 control women (54 of them were oral contraceptive users and 99 were non-users) were studied. The following hemostatic variables were measured: APTT, factor VII, factor VIII, factor XII, fibrinogen, prothrombin, total antithrombin, normalised activated protein C sensitivity ratio (n-APC-sr), protein C, protein S and free protein S. Results: We found marked and significant effects of oral contraceptive use on the levels of several clotting factors, with an increase in factor VII, factor XII, protein C and a decrease in antithrombin, n-APC-sr and protein S. Less marked effects that were non-significant or only significant in either patients or controls, were an increase in factor VIII, fibrinogen and prothrombin and a decrease in the APTT and free protein S. In the former thrombosis patients several of these effects of oral contraceptives were more pronounced than in healthy women: specifically on factor VII, antithrombin, n-APC-sr and protein C. Conclusions: Our results of the effects of oral contraceptives generally confirm previous reports in healthy volunteers. Our data also show that in former deep-vein thrombosis patients these effects are more pronounced. Apparently some women become “high hemostatic responders” when exposed to oral contraceptives, and they may be the women most vulnerable to its thrombogenic effects.